Alangkah indahnya salju (Kuala Lumpur : Dewan Bahasa dan Pustaka, 2003)
Prize winning poems and short stories in the poems and short stories writing contest of Dewan Bahasa dan Pustaka, Malaysia
Poems and short stories
Keywords: Short stories, Malay; Malay fiction; Malay literature